2021
DOI: 10.1037/tra0001014
|View full text |Cite
|
Sign up to set email alerts
|

Parental PTSD and psychological reactions during the COVID-19 pandemic among offspring of Holocaust survivors.

Abstract: Objective: Previous evidence suggests heightened sensitivity to life-threatening challenges among offspring of Holocaust survivors (OHS). Therefore, this study examined the psychological reactions of aging OHS during the COVID-19 pandemic. Method: A convenience sample (N = 297, mean age = 66.85) of North American Jews rated posttraumatic stress disorder (PTSD) symptoms for their parents and for themselves. They further rated their psychological distress, COVID-19-related worries, loneliness, and social support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 39 publications
(55 reference statements)
3
8
0
Order By: Relevance
“…These results correspond with the pattern of Holocaust G1, mentioned above, of high risk of distress due to repeated threats of terror and war (Dekel & Hobfoll, 2007). In general, Holocaust G1 demonstrated higher distress when confronted with additional stress (Kimron & Cohen, 2012), which was similarly reported in subsequent generations (Baider et al, 2000;Shrira & Felsen, 2021;Solomon et al, 1988). From this viewpoint, the current findings strengthen a model of resilience and vulnerability in three generations of Holocaust survivor families, in which vulnerability predominately develops when faced with traumatic or stressful experiences (Shrira, 2015).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These results correspond with the pattern of Holocaust G1, mentioned above, of high risk of distress due to repeated threats of terror and war (Dekel & Hobfoll, 2007). In general, Holocaust G1 demonstrated higher distress when confronted with additional stress (Kimron & Cohen, 2012), which was similarly reported in subsequent generations (Baider et al, 2000;Shrira & Felsen, 2021;Solomon et al, 1988). From this viewpoint, the current findings strengthen a model of resilience and vulnerability in three generations of Holocaust survivor families, in which vulnerability predominately develops when faced with traumatic or stressful experiences (Shrira, 2015).…”
Section: Discussionsupporting
confidence: 88%
“…Specifically, research in Holocaust survivor families indicate that Holocaust G2 are more perturbed about existent and probable threats (Shrira, 2015). Studies show vulnerability in Holocaust G2 when confronted with stressful life events and life-threatening circumstances including combat (Solomon et al, 1988), cancer (Baider et al, 2000), and the COVID-19 pandemic (Shrira & Felsen, 2021). Correspondingly, two studies underscored vulnerability among Holocaust G2 relative to comparisons in the face of the Iranian nuclear threat on Israel (Shrira, 2015).…”
Section: The Transmission Of Holocaust Traumamentioning
confidence: 99%
“…There is ample evidence that many communities that have experienced HT face ongoing oppression and discrimination (e.g., refugees, Hajak et al, 2021; Black Americans, Jones et al, 2020). Furthermore, currently the most supported transgenerational impact of trauma in the population-specific literature is a heightened reactivity to stress (e.g., Shrira & Felsen, 2021), suggesting that any comprehensive model of HT and its effects must consider potential current stressors, especially ongoing experiences of racism and religious discrimination.…”
Section: The Hitt Modelmentioning
confidence: 99%
“…Nevertheless, a more recent meta-analytic review indicated higher posttraumatic stress disorder (PTSD) symptoms among Holocaust G2 relative to comparisons (Payne & Berle, 2021). Other researchers have identified vulnerability among Holocaust G2 when coping with stressful life events and life-threatening circumstances (e.g., Baider et al, 2000; Shrira & Felsen, 2021; Solomon et al, 1988), indicating a combination of resilience and vulnerability (Giladi & Bell, 2013). This dispute is notable globally, as the long-term consequences of the Holocaust have ramifications in a widespread context of trauma among older survivors of atrocities around the world (Greenblatt-Kimron, 2021) and underscores the long-term effects of trauma on individuals and families in other trauma-exposed groups including families of Cambodian survivors of the Khmer Rouge Regime (Lin & Suyemoto, 2016), American Indian native groups (Hartmann & Gone, 2016), children in Northern Ireland (McNally, 2014), and survivors of political violence in Lithuania (Kazlauskas et al, 2017).…”
Section: Secondary Traumatization In Holocaust G2mentioning
confidence: 99%